VALUE RELEVANCE ATAS INFORMASI AKUNTANSI SEBELUM DAN SESUDAH ADOPSI IFRS PADA PERUSAHAAN MANUFAKTUR DALAM SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Karina Novitasari; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
This study aimed to know the influence of IFRS adoption on value relevance of accounting information presented with earnings per share (EPS), book value per share (BVPS), and operating cash flow per share (OCFS) as reflected by stock price changes. This study looked at the value relevance of accounting information during the two periods before and after the adoption of IFRS. The value relevance was based on the explanatory power (R2) of the stock price regression on EPS, BVPS and OCFS reflected from the R-squared value introduced by Ohlson. This research was in the form of quantitative research where the data used in this research were secondary data. This study used panel data that were companies in the consumer goods industry sector listed on the BEI from 2007 to 2014. The sample used in this research was consumer goods sector companies listed in Indonesia Stock Exchange and adopted IFRS in 2011. Sample amounted to 17 companies in 2007-2014. The data analysis techniques used was multiple regression model with software STATA version 14. The results showed that there was an increase on value relevance of accounting information presented with EPS, BVPS and OCFS reflected in changes in stock price. The research results were useful for the regulators, investors and standard-setters in Indonesia.